Global Transmission of Interest Rates : Monetary Independence and the Currency Regime - Schmukler, Sergio L. 1997- (The World Bank, 2000)
August 2000 - Hikes in U.S. interest rates in 1999-2000 have started to spill over to other economies' interest rates, which in many countries have risen to reflect the higher U.S. rates. Are countries with flexible exchange rates better able to isolate their domestic interest rates from this type of negative international shock? Less and less so, as economies become more integrated. Frankel, Schmukler, and Servén empirically study the sensitivity of local interest rates to international interest rates and how that sensitivity is affected by a country's choice of exchange rate regime. To establish the empirical regularities, they use a reduced-form empirical approach to compute both panel and single-country estimates of interest rate sensitivity for a large sample of developing and industrial economies between 1970 and 1999. When using the full sample, they find that: · Interest rates are typically lower in economies with fixed exchange rates than in those with flexible exchange rates. · More rigid currency regimes tend to exhibit higher transmission than more flexible regimes. In many cases in the 1990s, however, the authors cannot reject full transmission (a slope coefficient equal to 1), even for several countries with floating regimes. The data suggest an upward time trend in the degree to which domestic interest rates are sensitive to international capital movements and developing economies' increased financial integration with the rest of the world.